Prenatal maternal stress predicts stress reactivity at 2½ years of age: The Iowa Flood Study. (June 2015) - Yong Ping, Erin; Laplante, David P.; Elgbeili, Guillaume; Hillerer, Katharina M.; Brunet, Alain; O'Hara, Michael W.; King, Suzanne
Highlights: Toddler salivary cortisol levels increased in response to brief maternal separation. PNMS predicted greater cortisol reactivity in female toddlers. PNMS leads to long-term alterations in the functioning of the HPA axis. Disaster-related PNMS reprograms foetal development of the HPA axis. Summary: Prenatal maternal stress (PNMS) predicts psychosocial development in offspring. It has been hypothesized that during PNMS, glucocorticoids pass the placenta, reaching the foetus, leading to a long-term reprogramming and dysregulation of the foetal hypothalamic-pituitary-adrenal (HPA) axis. However, results are inconsistent across PNMS studies. One problem may be the confounding of objective degrees of hardship due to the stressor and subjective degrees of distress in the mother. The present study investigated the association between objective and subjective PNMS due to a natural disaster, the June 2008 Iowa floods, and stress reactivity in the offspring at 2½ years of age. Women who were pregnant during the floods were recruited, on average, within three months of the floods and their stress levels assessed. Mothers and their toddlers ( n = 94 dyads) participated in a brief mother–toddler separation to induce physiological stress responses in the offspring. Salivary cortisol samples were collected four times during the procedure. We computed absolute change in cortisol (baseline to 20-minute post-stressor; baseline to 45-minute post-stressor) and Area Under the Curve with respect to increase and ground (AUCi; AUCg). Objective and subjective PNMS were positively correlated with AUCi, as was timing in gestation: the later in pregnancy the exposure occurred, the greater the cortisol increase. Controlling for objective hardship and other covariates, sex-by-subjective PNMS interactions showed a significant and positive association between subjective PNMS and Absolute Increase (45 min) and AUCi in females only, with little effect in males. These results suggest that PNMS leads to long-term alterations in the functioning of the HPA axis, evident as early as 30-months of age.